ANALISIS YURIDIS TERHADAP PENETAPAN PENGADILAN MENGENAI PERUBAHAN STATUS JENIS KELAMIN (PERKARA NOMOR: 167/PDT.P/2018/PN.Skw) - VINDI HIU NARDI NIM. A1012181264 (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACTCourt decisions that meet the concept and strong legal basis are decisions that have legal considerations based on legal facts and clear and carefully made basic foundations. In cases of changing gender status in Indonesia due to sexual disorders, sexual disorders are caused by abnormalities in a person's hormones, transsexuals have the desire to change their sex using surgery. this can be done by applicable procedures. Until now, Indonesia does not have specific legal arrangements regarding changes in the gender status of a transgender person who performs gender operations. Changes in gender status can be made by submitting the request to the district court. Therefore the author takes the title